NUCLEOSOME ORGANIZATION IN PLANT DNA SATELLITES - V. N. Babenko; K. O. Kutashev; V. F. Matvienko (Вавиловский журнал генетики и селекции)
Satellite DNA, consisting of tandem repeats, forms heterochromatic regions packed into nucleosomes. Sequence and conformational DNA features responsible for the high efficiency of this package have been sought with a Fourier transform. The curvature profiles in tandem repeats differ significantly from a random model. As many as 50 % of the monomers have a periodicity of DNA bends in the vicinity of 170 bp, fitting the wrapping length of a single nucleosome within two highest-order harmonics in the DNA curvature profile. The nucleosome positioning scheme in subtelomeric satellites in plants differs from that in centromeric satellites.